Disrupting Parietal Function Prolongs Dominance Durations in Binocular Rivalry - Zaretskaya, Natalia; Thielscher, Axel; Logothetis, Nikos K.; Bartels, Andreas (Current biology, 2010)
Human brain imaging studies of bistable perceptual phenomena revealed that frontal and parietal areas are activated during perceptual switches between the two conflicting percepts [1–3]. However, these studies do not provide information about causality, i.e., whether activity reports a consequence or a cause of the perceptual change. Here we used functional magnetic resonance imaging to individually localize four parietal regions involved in perceptual switches during binocular rivalry in 15 subjects and subsequently disturbed their neural processing and that of a control site using 2 Hz repetitive transcranial magnetic stimulation (TMS) during binocular rivalry. We found that TMS over one of the sites, the right intraparietal sulcus (IPS), prolonged the periods of stable percepts. Additionally, the more lateralized the blood oxygen level-dependent signal was in IPS, the more lateralized the TMS effects were. Lateralization varied considerably across subjects, with a right-hemispheric bias. Control replay experiments rule out nonspecific effects of TMS on task performance, reaction times, or eye blinks. Our results thus demonstrate a causal, destabilizing, and individually lateralized effect of normal IPS function on perceptual continuity in rivalry. This is in accord with a role of IPS in perceptual selection, relating its role in rivalrous perception to that in attention [4–6]. ► TMS over the right intraparietal sulcus prolongs the periods of perceptual stability ► The degree of lateralization of parietal function varies across subjects ► fMRI signal strength and TMS effect size are related across subjects